Parabrachial nucleus astrocytes regulate wakefulness and isoflurane anesthesia in mice - Liu, Pei-Chang; Yao, Wei; Chen, Xing-Yu; Su, Wei-Kun; Zheng, Ze-Hong; Yan, Xiong-Bin; Deng, Ya-Ling; Shi, Kai-Ge; Liu, Xin; Gao, Yu-Wei; Lin, Tian-Tian; Zhu, Yun-Xi; et al. (Frontiers in Pharmacology, 2023)
Background: The parabrachial nucleus (PBN) is an important structure regulating the sleep–wake behavior and general anesthesia. Astrocytes in the central nervous system modulate neuronal activity and consequential behavior. However, the specific role of the parabrachial nucleus astrocytes in regulating the sleep-wake behavior and general anesthesia remains unclear. Methods: We used chemogenetic approach to activate or inhibit the activity of PBN astrocytes by injecting AAV-GFAabc1d-hM3Dq-eGFP or AAV-GFAabc1d-hM4Di-eGFP into the PBN. We investigated the effects of intraperitoneal injection of CNO or vehicle on the amount of wakefulness, NREM sleep and REM sleep in sleep–wake behavior, and on the time of loss of righting reflex, time of recovery of righting reflex, sensitivity to isoflurane, electroencephalogram (EEG) power spectrum and burst suppression ratio (BSR) in isoflurane anesthesia. Results: The activation of PBN astrocytes increased wakefulness amount for 4 h, while the inhibition of PBN astrocytes decreased total amount of wakefulness during the 3-hour post-injection period. Chemogenetic activation of PBN astrocytes decreased isoflurane sensitivity and shortened the emergence time from isoflurane-induced general anesthesia. Cortical EEG recordings revealed that PBN astrocyte activation decreased the EEG delta power and BSR during isoflurane anesthesia. Chemogenetic Inhibition of PBN astrocytes increased the EEG delta power and BSR during isoflurane anesthesia. Conclusion: PBN astrocytes are a key neural substrate regulating wakefulness and emergence from isoflurane anesthesia.